2008
DOI: 10.1016/j.lfs.2008.09.023
|View full text |Cite
|
Sign up to set email alerts
|

In vivo trafficking of endogenous opioid receptors

Abstract: Several approaches have been taken for these in vivo studies. In many studies, the use of semiquantitative immuno-electron microscopy is the approach of choice. Endogenous opioid receptors display differential subcellular distributions with µ opioid receptor (MOPR) being mostly present on the plasma membrane and δ-and κ-opioid receptors (DOPR and KOPR, respectively) having a significant intracellular pool. Etorphine and DAMGO cause endocytosis of the MOPR, but morphine does not, except in some dendrites. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Absence of ␤ 3 -AR desensitization, first found in recombinant expression systems (Nantel et al, 1993), was confirmed in an endogenous cell system (Jockers et al, 1998). Similar findings were reported for the -opioid (Wang et al, 2008) and the somatostatin-4 receptor (Schreff et al, 2000), indicating that lack of receptor endocytosis is not an artifact per se because of heterologous protein expression.…”
Section: Discussionsupporting
confidence: 64%
“…Absence of ␤ 3 -AR desensitization, first found in recombinant expression systems (Nantel et al, 1993), was confirmed in an endogenous cell system (Jockers et al, 1998). Similar findings were reported for the -opioid (Wang et al, 2008) and the somatostatin-4 receptor (Schreff et al, 2000), indicating that lack of receptor endocytosis is not an artifact per se because of heterologous protein expression.…”
Section: Discussionsupporting
confidence: 64%
“…Desensitized and internalized KOPrs are expected to either resensitize and recycle back to the surface membrane, or be sorted to degradation pathways leading to downregulation (Wang et al 2008 and references there in). In neurons, the majority of KOPrs is located in the cytosol and this receptor pool might influence KOPr trafficking by facilitating the insertion of new receptors into the cell surface membrane (Svingos and Colago 2002;Wang et al 2008 and discussion there in). Hence, it is theoretically possible that prolonged agonist administration in vivo not to down-regulate KOPrs, since degraded receptors could be continuously replaced from a compensatorily maintained intracellular receptor pool.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite the DOPr desensitization in NAc shell and core, no receptor downregulation was evident. Little is known about the trafficking of DOPrs in vivo (Wang et al 2008 and references therein). It has been suggested that DOPrs are slowly recycled/ degraded after agonist-induced internalization in vivo (Pradhan et al 2009), and there is evidence in vitro that the post-endocytotic fate of the receptors is influenced by the type of agonist with the natural enkephalins promoting recycling and resensitization of receptor (Lecoq et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, receptor externalization is the preferable route following long-term pharmacological manipulation of the endogenous ligand in vivo. In striatal neurons, the majority of DOPrs is located in the cytosol (Wang and Pickel 2001;Wang et al 2008 and discussion therein), and a compensatorily maintained intracellular receptor pool during prolonged agonist exposure might influence DOPr trafficking by facilitating the insertion of new receptors into the cell surface membrane. The observation that the receptor mRNA in NAc shell tended to rise over the time indicates that compensatory receptor protein synthesis may occur in order to maintain receptor number.…”
Section: Discussionmentioning
confidence: 99%